2014
DOI: 10.1111/1754-9485.12169
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian tube recanalisation using dedicated radiographic tubal assessment set in angiography suite

Abstract: Selective salpingography and FTR using FluoroSet(®) is a safe and effective method. FTR is recommended as the first intervention in patients with PFTO. In experienced hands with dedicated equipment and in an appropriate setting, the success rate is high, and this treatment should be offered to infertile women with PFTO before other, more complex techniques are attempted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…After the introduction of FTR as a treatment for proximal FTO [ 8 ], several studies have confirmed the safety and efficacy of this procedure [ 8 , 9 , 10 ]. However, there is substantial variation in the reported technical success rates and pregnancy rates following FTR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After the introduction of FTR as a treatment for proximal FTO [ 8 ], several studies have confirmed the safety and efficacy of this procedure [ 8 , 9 , 10 ]. However, there is substantial variation in the reported technical success rates and pregnancy rates following FTR.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is substantial variation in the reported technical success rates and pregnancy rates following FTR. Reported variations in technical success rates may be attributed to operator experience, tools, and equipment used [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations